“PERBANDINGAN FORMASI TEMPAT DUDUK TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS V SDN 52 PANGKALPINANG - Anita Safitri; Asyraf Suryadin; Said Akhmad Maulana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Classroom environment management, particularly the design of seating arrangements, is an essential element in fostering student participation dynamics and optimizing academic achievement, especially in the context of Indonesian language subjects that demand intensive interaction. This study systematically compares the influence of U-shaped seating formations with traditional models on the learning abilities of fifth-grade students at SDN 52 Pangkalpinang. The research employed a quantitative approach, implemented through a pre-experimental one- group posttest-only design, with participants consisting of all 28 students of class V A using a total sampling technique. Data collection instruments included pretests and posttests, facilitated by cognitive tests and subjective questionnaires to capture perceptual dimensions. The data analysis stage covered normality testing, examination of supporting conditions, and hypothesis validation using the Paired- Sample T test to ensure interpretive accuracy. Empirically, differences in learning scores were found to be significant, with the U-shaped formation producing higher average scores than the traditional model, as confirmed by a significance level of 0.000 (p < 0.05) and a t-value of 4.900 exceeding the t-table value of 2.052— indicating a reliable improvement. In contrast, questionnaire data regarding student perceptions revealed no meaningful disparity, based on a significance value of 0.374 (p > 0.05) and a t-value of 0.904 below the t-table value of 2.052, indicating consistency in students’ views across seating arrangements. Therefore, with Ha accepted and Ho rejected, this study concludes that the comparison between U- shaped and traditional seating formations has a substantial impact on Indonesian language learning achievement in fifth grade at SDN 52 Pangkalpinang, opening opportunities for more inclusive pedagogical innovations in primary education